2021
DOI: 10.1016/j.jbusres.2020.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Omnichannel battle between Amazon and Walmart: Is the focus on delivery the best strategy?

Abstract: A large body of academic research has recently focused on omnichannel retailing especially on brick-and-mortar (offline) retailers adding and integrating online capabilities. Relatedly, trade press has highlighted how offline retailers have been investing heavily in the use of their existing physical retail network for quicker delivery and pick-up of online orders. Looking at the competition between Amazon and Walmart, however, we demonstrate that focusing on quicker delivery is not the best strategy for offli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…In particular, multiple touchpoint shoppers and online-to-offline shoppers provide an attractive option for omnichannel businesses as they already use digital and physical channels and would appreciate a seamless customer journey. Similarly, omnichannel retailers might target younger double-income households with higher levels of education and income, as they seem the most receptive to adopting retailers' newer channels (Jindal et al, 2021).…”
Section: Research Theme 1: Strategy and Transition To Omnichannel Businessmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, multiple touchpoint shoppers and online-to-offline shoppers provide an attractive option for omnichannel businesses as they already use digital and physical channels and would appreciate a seamless customer journey. Similarly, omnichannel retailers might target younger double-income households with higher levels of education and income, as they seem the most receptive to adopting retailers' newer channels (Jindal et al, 2021).…”
Section: Research Theme 1: Strategy and Transition To Omnichannel Businessmentioning
confidence: 99%
“…The positive effects of channel integration in the transaction phase (i.e., offering in-store pickup after an online purchase) on channel choice can be attributed to providing real-time information about inventory availability and reducing the hassle cost of shopping (Gao & Su, 2017). Interestingly, the factors influencing consumers' choice of omnichannel services (e.g., home delivery of online orders, picking up online orders in store) differ between physical-first (i.e., Walmart) and digital-first retailers (i.e., Amazon) (Jindal et al, 2021). Turning to post-transaction services, Miquel-Romero et al ( 2020) focus on channel choice for post-purchase complaints.…”
Section: Research Theme 2: Management Of Omnichannel Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to properly manage the trade-off between cost and service is demonstrated by the attempt by many companies to adopt alternative delivery solutions in which a lower transportation cost is coupled with an acceptable service level for the customer (Jindal et al, 2021). Examples are such systems as Click&Collect, Click&Reserve, Click&Drive, and attended and unattended pick-up points and lockers (Cao & Li, 2015).…”
Section: Supply Chain Management Perspectivementioning
confidence: 99%
“…Benjamin and Wingand thought that platform enterprise offered a cost-effective distribution channel and greatly reduced the logistics costs [2]. Through studying the strategies of Amazon and Walmart, Jindal et al found that providing more kinds of products, competitive prices, and convenient ways to purchase for online users are the best strategies to improve competitiveness [3]. However, Oliva et al found that low pricing and rapid expansion of the market would generate negative feedback to platform enterprises in the long term [4].…”
Section: Literature Reviewmentioning
confidence: 99%